Governance Reform in Services Security and Order of Visit at Prison - Rozikin, Mochammad; Rustanto, Agung Edi; Rustanto, Agung Edi; Hakim, Abdul; Wike, (International Journal of Psychosocial Rehabilitation, 2020)
In general, prisons in Indonesia are attributed to overcapacity and a horrible standard facility, but there is one prison found the opposite problem. Still, instead, prisoners can enjoy luxury facilities that exceed the standard. One of the luxurious facilities enjoyed by the prisoneris the facility to receive visits. A prisonerin class 1 of Sukamiskinprison can receive visits with luxury facilities in the form of luxury halls built by the prisoners. Prisoners can order fancy foods from the restaurant to be sent to prison.Another problem is that the visit time is not according to the rules, where a prisonercan be visited until late at night. The irregularity of the visit to class 1 of Sukamiskinprison received the attention of the community. The Ministry of Law and Human Rights is urged to carry out governance reforms to improve security services and order traffic. Governance reform in Sukamiskinclass 1 prison is carried out through several effective stages. The success of governance reforms in security services and orderliness of visits needs to be examined because it is essential to know the implementation process. This research applied the descriptive qualitative method with a case study approach in class 1 ofSukamiskin prison. Informants in this study were prison leadership officials, prison staff officers, prisoners, and visitors. The results of this study are governance reforms inclass 1 of Sukamiskin prison succeeded in creating a safer and more orderly visit service. The entire visit service is carried out following the standards, both the facilities and the time of the visit.